Advances in Peritoneal Dialysis in Acute Kidney Injury - Ponce, Daniela [UNESP]; Zamoner, Welder [UNESP]; Dias, Dayana Bitencourt [UNESP]; Banin, Vanessa [UNESP]; Balbi, Andre Luis [UNESP] (Elsevier, 2023)
UNASSIGNED: In the 1970s, acute peritoneal dialysis (PD) was widely accepted for the treatment of acute kidney injury (AKI), but this practice has declined in favor of extracorporeal therapies, mainly in developed world. The lack of familiarity with the use of PD in critically ill patients has also led to a lack of use even among those receiving maintenance PD. Renewed interest in the use of PD for AKI therapy has emerged due to its increasing use in low- and middle-income countries due to its lower cost and minimal infrastructural requirements. In high-income countries, the coronavirus disease 2019 pandemic saw PD for AKI used early on, where many critical care units were in crisis and relied on PD use when resources for other AKI therapy modalities were limited. In this review, we highlight the advantages and disadvantages of PD in AKI patients and indications and contraindications for its use. We also provide an overview of advances to support PD treatment during AKI, discussing PD access, PD prescription, complications related to PD, and its use in particular clinical conditions. (Rev Invest Clin. 2023;75(6):327-36).
Keywords: Acute kidney injury; Critically ill patients; Dialysis; Peritoneal dialysis